Transition dipole moments and transition probabilities of the NS radical. (June 2019) - Zhou, Dan; Shi, Deheng; Sun, Jinfeng
Highlights: Radiative lifetimes are of the order 10 −6 s for the B 2 Π state. B 2 Π–X 2 Π, B′ 2 Σ + –X 2 Π, and b 4 Σ − –a 4 Π transitions are strong. Radiative lifetimes are approximately 10 −5 –10 −6 s for the B′Σ + state. Radiative lifetimes are approximately 10 −4 –10 −5 s for the b 4 Σ − state. Rovibrational transitions are discussed for several-pair Ω states. Abstract: In this work, spectroscopic parameters and transition properties are studied for the X 2 Π, B 2 Π, B′ 2 Σ +, a 4 Π, and b 4 Σ − states of the NS radical. It is found that the rotationless radiative lifetimes of the vibrational levels are approximately several µs for the B 2 Π state, in order of 10 µs for the B ′Σ + state, and 10 to 100 µs for the b 4 Σ − state. Therefore, vibronic emissions originating from them occur readily. The Einstein coefficients of the vibronic emissions from the B 2 Π–X 2 Π, B ′ 2 Σ + –X 2 Π, and b 4 Σ − –a 4 Π are large, indicating that the transitions of these systems can be measured readily through spectroscopy. The effect of the spin–orbit coupling effect on the spectroscopic parameters is evaluated for these five states. The splitting energies of the X 2 Π and B 2 Π states are 221.67 and 95.05 cm −1 at the internuclear equilibrium positions, respectively. The transition properties for each pair of Ω states are calculated and the results calculated compared with available experimental ones. The spectral range of vibronic emissions is determined for the transitions of several- pair Ω states. Graphical abstract: Image, graphical abstract The radiative lifetimes are of the orders of 10 −6, 10 −5 –10 −6, and 10 −4 –10 −5 s for the vibrational levels of B 2 Π, B′ Σ +, and b 4 Σ − states of the NS radical, suggesting that the vibronic emissions generated from these states occur easily. The B 2 Π–X 2 Π, B′ 2 Σ + –X 2 Π, and b 4 Σ − –a 4 Π transitions are strong. Rovibrational transitions are calculated for several- pair Ω states. Overall, the spin–orbit coupling effect on the spectroscopic parameters and vibrational properties of this radical is not large.